Physiological condition status and muscle-based biomarkers in rainbow trout (Oncorhynchus mykiss), after long-term exposure to carbamazepine - Li, Zhi-Hua; Zlabek, Vladimir; Velisek, Josef; Grabic, Roman; Machova, Jana; Randak, Tomas (Journal of applied toxicology, 2010)
Recently, residual pharmaceuticals are generally recognized as relevant sources of aquatic environmental pollutants. However, the toxicological effects of these contaminants have not been adequately researched. In this study, the chronic toxic effects of carbamazepine (CBZ), an anticonvulsant pharmaceutical commonly present in surface and ground water, on physiological condition status and muscle-based biomarkers of rainbow trout were investigated. Fish were exposed at sublethal concentrations of CBZ (1.0 microg l(-1), 0.2 mg l(-1) and 2.0 mg l(-1)) for 42 days. Compared with the control, there was a significant lower (P < 0.05) condition factor in fish exposed at the highest concentration of CBZ (2.0 mg l(-1)), but the hepatosomatic indices in all groups were not significant changes. At lower CBZ concentration (1.0 microg l(-1), 0.2 mg l(-1)), the antioxidant enzyme activities were induced slightly, except catalase, while at the highest concentration (2.0 mg l(-1)) oxidative stress was apparent as reflected by the significant higher lipid peroxidation and protein carbonyls in the fish muscle, associated with a significant inhibition of antioxidant enzymes activities. Moreover, energy metabolic parameters (RNA-DNA ratio, Na(+)-K(+)-ATPase) were significantly inhibited in muscle of the fish exposed at the highest concentration (2.0 mg l(-1)), compared with the control. In short, CBZ-induced physiological and biochemical responses in fish were reflected in parameters measured in this study, which suggest that these biomarkers could be used as potential indicators for monitoring residual pharmaceuticals present in aquatic environment.
Keywords: chemické látky znečišťující vodu; Carbamazepine; velikost orgánu; Oncorhynchus mykiss; Glutathione Reductase; karbonylace proteinů; sodíko-draslíková ATPasa; Male; biologické markery; superoxiddismutasa; Organ Size; Biomarkers; náhodné rozdělení; látky reagující s kyselinou thiobarbiturovou; glutathionperoxidasa; vztah mezi dávkou a účinkem léčiva; Water Pollutants, Chemical; Muscle, Skeletal; Thiobarbituric Acid Reactive Substances; Protein Carbonylation; mužské pohlaví; algoritmy; Anticonvulsants; Body Weight; Catalase; kosterní svaly; Animals; karbamazepin; RNA; ženské pohlaví; játra; Sodium-Potassium-Exchanging ATPase; zvířata; katalasa; glutathionreduktasa; antikonvulziva; Random Allocation; Algorithms; DNA; Superoxide Dismutase; Glutathione Peroxidase; Liver; Female; Dose-Response Relationship, Drug; tělesná hmotnost